Feminism Reality as Expressed by Sumarni in the Years of The Voiceless Novel by Okky Madasari: A Critical Discourse Analysis - Ayu Monita Eka Shinta (Universitas Dian Nuswantoro, 2018)
This thesis entitled Feminism Reality as Expressed by Sumarni in the Years of the Voiceless Novel by Okky Madasari: A Critical Discourse Analysis is conducted to convey position and feminism reality of woman as reflected by Sumarni in this novel. The subject of this study is the main character namely Sumarni regarded as a voiced civilian woman. The reason for choosing this novel is because of inequality power relation issues, especially woman. Women are considered as weak. Here, Sumarni appears as a main character who wants to speak up rather than to be voiceless. This study is intended to give a model in how woman can show her power through her utterances since woman wants to be equal in society. There were several steps in doing this study which have been done. Under the qualitative research, the data collection started from reading the novel and then selecting utterances. While the method of data analysis was done by grouping Sumarni’s utterances, after that the utterances were analyzed by considering feminist stylistic elements at the level of sentence by using transitivity choices and Wodak’s triangulatory approach. The result of this study reveals that the use of relational process is higher than material process intention and supervention, and mental process internalized and externalized. From the finding above, it can be seen that Sumarni appears as a not common woman since she can be a sugarcane field owner and moneylender in the end of the novel. In addition, there is a feminism reality as realized by Sumarni that a woman must be independent and be responsible both in society and family. Keywords: CDA, feminist stylistics, feminism, The Years of the Voiceless, utterances Women